Efek Ekstrak Etanol Buah Dewandaru (Eugenia uniflora L) terhadap Penurunan Kadar Glukosa Darah dan Perbaikan Sel Beta Pankreas pada Mencit yang Diinduksi Aloksan - Maharani, Ade Dwi Karisma; Santoso, Puguh; Udayani, Ni Nyoman Wahyu (Usadha, 2023)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia resulting from impaired insulin secretion. Dewandaru fruit (Eugenia uniflora L.) contains flavonoids which act as free radical scavengers and reduce oxidative stress. This study aims to prove that the administration of ethanol extract of dewadaru fruit at doses of 200 mg/KgBW and 400 mg/KgB can reduce blood glucose levels and repair damage to pancreatic β cells in alloxan-induced male white mice (Rattus norvegicus) wistar strain diabetes mellitus. This study used 32 mice aged 2-3 months weighing 25 grams intraperitoneally induced by alloxan (0.5 ml/kg). Mice were divided into four treatment groups, namely K- (alloxan), K+ (glibenclamide), P1 (dose of dewadaru fruit extract 200 mg/kgBB), P2 (dose of dewadaru fruit extract 400 mg/kgBB) Quantitative data by calculating blood glucose levels and the number of pancreatic β cells were analyzed using Paired T-Test. P2 is the dose of dewadaru fruit extract 400 mg/kg BW. In the repair of pancreatic β cells it was stated that the average damage to pancreatic β cells at a dose of 200 mg/KgBB was 67.5 and at a dose of 400 mg/KgBW was 89.1. This study proves that the ethanol extract of dewadaru fruit is able to lower blood glucose and inhibit the rate of damage to pancreatic β cells in mice with diabetes mellitus. Keywords: dewadaru, diabetes mellitus, blood glucose, pancreatic β cells